(untitled) (Innovation & Development in Engineering and Applied Science, 2025)
The research focuses on the design and construction of a modular teaching platform for microcontroller and embedded systems laboratories at a university. The platform consists of 20 modules with silkscreen printed components, communication ports and power supply. It communicates with the PC through a USB port, processing the information of the entire modular platform. The design and components used were selected in response to the real needs of teachers and students, gathered through surveys. In addition, the platform allows the integration of these subjects in the simulation of technological processes and the intelligent control of a house. The results show that the modular platform has improved the teaching-learning process, applying theoretical concepts in real environments. It works with Arduino IDE software and free hardware. Its design is ergonomic and didactic for each prototype station of each circuit. Its dimensions are 555 mm long by 355 mm wide, which facilitates its mobilization. The power supply of the boards is included and is indicated with a voltage of 5 V and 3.3 V. It is optimal in practice development time, circuit design and reduction of unnecessary expenses for students. The effectiveness of the project was evaluated through performance evaluations, satisfaction surveys and development of laboratory guides in areas such as automation, control and power.